The arithmetic sequence formula is used for the calculation of the n^{th} term and sum of an arithmetic progression. The arithmetic sequence is the sequence where the common difference remains constant between any two successive terms. If we want to find any term/the sum of terms in the arithmetic sequence then we can use the arithmetic sequence formula. Let us understand the arithmetic sequence formula using solved examples.

## What is the Arithmetic Sequence Formula?

An arithmetic sequence is of the form: a, a + d, a + 2d, a + 3d,......up to n terms. The first term is a, the common difference is d, n = the number of terms. For the calculation using the arithmetic sequence formulas, first identify the first term, the number of terms and the common difference of the sequence. There are different formulas associated with an arithmetic series used to calculate the n^{th} term, sum, or the common difference of a given arithmetic sequence.

- nth term is, a
_{n}= a_{1}+ (n - 1) d - Sum of n terms is, S
_{n}= (n/2) [2a_{1}+ (n - 1) d] (or) (n/2) [a_{1}+ a_{n}] - Common difference, d = a
_{n}- a_{n - 1}

In these formulas, a_{1} = the first term, d = common difference, and n = number of terms.

### Arithmetic Sequence Formula

The arithmetic sequence formulas are given as,

**Formula 1:** The **arithmetic sequence formula **to find the n^{th} term is given as,

a_{n} = a_{1} + (n - 1) d

where,

- a
_{n}= n^{th}term, - a
_{1}= first term, and - d is the common difference

**Formula 2:** The sum of first n terms in an arithmetic sequence is calculated by using one of the following formulas:

- S
_{n}= (n/2) [2a_{1}+ (n - 1) d] (when we know the first term and the common difference) - S
_{n}=(n/2) [a_{1}+ a_{n}] (when the first and the last terms)

where,

- S
_{n}= Sum of n terms, - a
_{1}= first term, - a
_{n}= n^{th}term, and - d is the common difference between the successive terms

**Formula 3:** The formula for calculating the common difference of an arithmetic sequence is given as,

d = a_{n} - a_{n - 1}

where,

- a
_{n}= n^{th}term, - a
_{n - 1}= (n - 1)^{th}term, and - d is the common difference between the successive terms

## Applications of Arithmetic Sequence Formula

We use the arithmetic sequence formula every day or even every minute without even realizing it. Given below are a few real-life applications of the arithmetic sequence formula

- Stacking the cups, chairs, bowls, or a house of cards.
- Seats in a stadium or an auditorium are arranged in an arithmetic sequence.
- The seconds' hand on the clock moves in arithmetic Sequence, and so do the minutes' hand and the hour's hand.
- The weeks in a month follow the arithmetic sequence, and so do the years. Each leap year can be determined by adding 4 to the previous leap year.
- The number of candles blown on a birthday increases as an arithmetic sequence every year.

Cuemath is one of the world's leading math learning platforms that offers LIVE 1-to-1 online math classes for grades K-12. Our mission is to transform the way children learn math, to help them excel in school and competitive exams. Our expert tutors conduct 2 or more live classes per week, at a pace that matches the child's learning needs.

Want to find complex math solutions within seconds?

Use our free online calculator to solve challenging questions. With Cuemath, find solutions in simple and easy steps.

Book a Free Trial Class

## Examples Using Arithmetic Sequence Formula

**Example 1:** Using the arithmetic sequence formula, find the 13^{th} term in the sequence 1, 5, 9, 13...

**Solution:**

To find: 13^{th} term of the given sequence.

Since the difference between consecutive terms is the same, the given sequence forms an arithmetic sequence.

a = 1, d = 4

Using arithmetic sequence formula,

a_{n} = a_{1}+ (n - 1) d

For 13^{th} term, n = 13

a_{n} = 1 + (13 - 1)4

a_{n} = 1 + (12)4

a_{n} = 1 + 48

a_{n} = 49

**☛ Also Check:** Arithmetic Sequence Calculator

**Answer:** 13^{th} term in the sequence is 49.

**Example 2:** Find the first term in the arithmetic sequence where the 35^{th} term is 687 and the common difference 14.

**Solution:**

To find: The first term in the arithmetic sequence

Given: a_{n} = n^{th} term, d = 14

Using arithmetic sequence formula,

a_{n} = a_{1} + (n − 1)d

687 = a_{1} + (35 - 1)14

687 = a_{1} + (34)14

687 = a_{1} + 476

a_{1} = 211

**Answer:** The first term in the sequence is 211.

**Example 3:** Find the sum of the following arithmetic series: 3 + 7 + 11 + ....... (up to 25 terms).

**Solution:**

To find the sum of the first 25 terms of the arithmetic sequence 3, 7, 11,.......

Given: a_{1} = 3, d = 4, n = 25

The given arithmetic sequence is 3, 7, 11,….

Using the arithmetic series formula:

S_{n} = (n/2) [2a + (n - 1) d]

The sum of the first 25 terms

S_{25}=(25/2) [2 x 3 + (25 - 1) 4]

= (25/2) [6 + 24 x 4]

= 25/2 × 102

= 1275

**Answer:** The sum of the given arithmetic series is 1275.

## FAQs on Arithmetic Sequence Formula

### What is Arithmetic Sequence Formula in Algebra?

The **arithmetic sequence formula** refers to the formula to calculate the general term of an arithmetic sequence and the sum of the n terms of an arithmetic sequence.

- The general term of an arithmetic sequence is, a
_{n}= a_{1}+ (n - 1) d - The sum of the first 'n' terms of an arithmetic sequence is,
_{n}= (n/2) [2a_{1}+ (n - 1) d]

where, a_{1} = the first term and d = common difference of the sequence.

### What is n in Arithmetic Sequence Formula?

In the arithmetic sequence formula for finding the general term, a_{n} = a_{1} + (n - 1) d, 'n' refers to the number of the term in the given arithmetic sequence. For example, a_{2} represents the 2^{nd} term of the sequence.

### What is the Arithmetic Sequences Formula for the Sum of n Terms?

The sum of the first n terms in an arithmetic sequence is given as, S_{n} = (n/2) [2a_{1} + (n - 1) d] where S_{n} = sum of n terms, a_{1} = first term, and d is the common difference.

### What is Arithmetic Series formula?

Arithmetic series is nothing but the sum of a few or all terms of an arithmetic sequence. Thus, the arithmetic series formula is:

- S
_{n}= (n/2) [2a_{1}+ (n - 1) d] [OR] - S
_{n}= (n/2) [a_{1}+ a_{n}]

Here, a_{1} is the first term of the arithmetic series and 'd' is its common difference.

### How To Use the Arithmetic Sequence Formula?

To use the arithmetic sequence formula, first identify the first term (a_{1}) and the common difference (d) of the sequence. Then substitute these in the relevant formula (of n^{th} term or the sum) and simplify.

### What is the Difference Between Explicit Formula and Recursive Formula of an Arithmetic Sequence?

The explicit formula is used to find any term of an arithmetic sequence if we just know its first term and the common difference. But the recursive formula can be used to find a term only when its previous term and common difference are known.

- The explicit formula for arithmetic sequence is, a
_{n}= a_{1}+ (n - 1) d - The recursive formula for arithmetic sequence is, a
_{n}= a_{n - 1}+ d